Persepsi Mahasiswa Tentang Kemampuan Dosen dalam Mendesain Pembelajaran Berbasis Integrasi Penelitian dan PKM (Studi Pada Mahasiswa Prodi PAI UINSU Medan) - Lubis, Rahmat Rifai; Nabila, Ridha; Citra, Yulia; Rahmaini, Siti (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi Pancor, 2023)
This study aims to analyze the ability of lecturers in designing learning based on the integration of research and PKM. The focus of the study in this research consists of two things, namely student perceptions and factors that influence the ability of lecturers. The research method used is qualitative with a descriptive study approach. Techniques used in data collection include observation, interviews, and documentation. Furthermore, to analyze the data, Miles and Huberman techniques were used, namely data reduction techniques, data presentation, and conclusion drawing. The results of the study explain that learning based on the integration of research and PKM has been implemented in UINSU's PAI study program but its application has not been maximized because only some lecturers have implemented it in totality. Supporting factors for the lecturers' ability to design learning based on the integration of research and PKM are student creativity and research and PKM works owned by lecturers. While the inhibiting factors of lecturers' ability to design learning based on the integration of research and PKM are some lecturers want to ease the duties of students because students are considered not able to do the learning as a whole.